GROUP ART THERAPY FOR CHILDREN DIAGNOSED WITH HIGH FUNCTIONING AUTISM SPECTRUM DISORDER: DESCRIPTION OFPROGRAM AND OUTCOMES - Krasno, Maayan (E-Journal VFU, 2024)
The current research examined the effects of a unique group art therapy, using phenomenological psychological methods, on the emotional and social skills of elementary school children (6-12 year old) diagnosed with High functioning Autism. Thirteen children, in three small groups, of different ages, who attend special education classes in regular schools in Israel participated in an eight-month weekly intervention. Before the beginning of the program, the art therapist conducted individual sessions with each child. Each group session included: movement activity, check in, a creative process and a phenomenological reflection discussion. According to interviews conducted with the children's parents, in all three groups the children exhibited improved social skills, self-confidence, flexibility and emotional competence. In the past such improvements were only found in older children learning specific social skills. This study demonstrated that children with HFA can benefit from a group art therapy and are able to reflect on their own and others' artwork.
Keywords: group art therapy; social skills; emotional competence; High functioning autism